Neurological changes in patients with Thrombotic Thrombocytopenic Purpura and ADAMTS13 deficiency: A case report (Research, Society and Development, 2024)
The objective of this article is to report a case of Thrombotic Thrombocytopenic Purpura (TTP) with significant neurological manifestations, highlighting the importance of early diagnosis and appropriate therapeutic management to improve patients' prognosis. Previously healthy adult patient, who presented symptoms of TTP in October 2022, 49 years old, was admitted with severe headache, disorientation and ecchymosis, associated with thrombocytopenia, microangiopathic hemolytic anemia and renal and cardiac impairment. The diagnosis of TTP was based on severe thrombocytopenia, hemolytic anemia, presence of schistocytes, elevated LDH and bilirubin, and reduced levels of ADAMTS13. Therapy included corticosteroids, caplacizumab and plasmapheresis, with partial clinical response. However, the patient developed new neurological manifestations, including dyslalia and cerebral ischemia, evidenced by computed tomography. The case analysis suggests that severe ADAMTS13 deficiency was the main factor related to the severity of neurological complications, even though there was a dissociation between the site of ischemia and the clinical presentation. This case study contributes to the literature by detailing a rare and serious episode of TTP with neurological complications, highlighting the need for rapid and precise interventions to prevent disease progression. Despite the limitations inherent to the single-case study, the findings reinforce the importance of immediate treatment, including plasmapheresis and immunosuppression, to reduce mortality and improve the recovery of patients with TTP.